QUANTITATIVE ASSESSMENT OF THE EFFECTIVENESS OF ANTI-CORRUPTION STRATEGIES IN CANDIDATE COUNTRIES FOR ACCESSION TO THE EUROPEAN UNION - Novoskoltseva, Lyudmila (Public Management and Policy, 2026)
This article provides a quantitative assessment of the effectiveness of anti-corruption strategies in European Union candidate states. The relevance of the study is driven by the fact that anti-corruption capacity constitutes one of the key prerequisites for meeting the political criteria for membership; however, the formal existence of strategies does not always reflect their actual performance. The study aims to develop an integral approach to the comparative assessment of anti-corruption strategy effectiveness in candidate countries and to identify country clusters by level of institutional performance. The methodology is based on a combination of index analysis, a comparative approach, content analysis of European Commission reports, and author-developed indicator normalization. The model incorporates four components: the level of corruption perception, the dynamics of change, the European Commission’s readiness assessment in the area of anti-corruption, and the practical effectiveness of law enforcement. The results demonstrate that Albania, Moldova, and Montenegro received the highest composite scores; however, their profiles differ considerably: Albania exhibits a stronger law enforcement component, Moldova shows the most favorable positive dynamics, and Montenegro displays a relatively stable institutional base. Ukraine occupied an intermediate position, which reflects a combination of a positive anti-corruption track record with limited progress and institutional resilience risks. The lowest scores were recorded for Turkey, Bosnia and Herzegovina, and Serbia, where formal anti-corruption constraints are not accompanied by sufficient public trust, stable dynamics, or credible law enforcement. The practical significance of the study lies in the potential use of the proposed index as a preliminary diagnostic tool for governments, public administration bodies, and expert communities.